An inspection path optimization of impeller for balancing efficiency and accuracy. (July 2019) - Wan, Neng; Jiang, Renzheng; Zhao, Heng; Zhang, Sentang
Highlights: The bidirectional rotations of the rotary axes are avoided as much as possible to decrease the inspection error. Multi-axis simultaneous ability of the on-machine probe is used to reduce the inspection path length. The accessible space is established not only on the inspection locations but also the locations between them. Abstract: On-machine inspection becomes a trend for obtaining the real shape of the workpiece in adaptive machining. Troubled by the overlapping structure of the impeller, and the positioning error from the rotary axes of the machine tool, it is a challenge to generate an on-machine inspection path to balance efficiency and accuracy. Reducing inspection path helps to reduce the occupied time of the machine tool. Thus, to let the stylus needn't leave the impeller's channel during the inspection, the accessible space of whole inspection path is addressed in path generation. In order to improve accuracy, the inspection error affected by the positioning errors of the rotary worktable is discussed. Furthermore, the error differences of the unidirectional and bidirectional rotations of the rotary axes are considered in path generation. By the stylus orientation optimization, the bidirectional rotations of rotary axes are prevented as much as possible. At last, the effectiveness of improving inspection efficiency and accuracy is verified by the impeller on-machine inspection. The inspection time can be reduced to less than 40% of traditional inspection, and the inspection error can be decreased 0.008 mm at least.